The association between night eating syndrome (nes) with body mass index (bmi) and demographic data among undergraduate students in Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan (USMKK) - Khairy, Muhammad Faris Fiqran Hairry Helmy @ (Universiti Sains Malaysia, 2024)
Night Eating Syndrome (NES) is an eating disorder characterized by recurrent episodes of excessive food consumption after dinner or nocturnal ingestion after rising from sleep, often accompanied by insomnia and mood swings. NES has garnered attention due to its potential impact on overall health, particularly its association with Body Mass Index (BMI) and obesity-related issues. This study examines the prevalence of Night Eating Syndrome (NES) and its association with Body Mass Index (BMI) and demographic characteristics among students at the USM Health Campus (USMKK). A cross-sectional study was conducted, with 97 participants completing self-reported online questionnaires, including the Night Eating Questionnaire (NEQ). The prevalence of NES was discovered to be 6.2%, with the majority of individuals being female (81.4%) and Malay (82.5%), with a median age of 22 years (IQR=2). The median BMI was 20.8 kg/m² (IQR=5.71), and 46.4% were categorised as having a normal BMI. Although the result showed the higher prevalence of students with NES within overweight and obese category, Fisher's Exact test revealed no significant association between NES status and BMI categories (p=0.06). The Spearman's correlation revealed no significant relationship between NEQ scores and BMI (p=0.14). Furthermore, no significant relationships were discovered between NES and demographic variables such as gender, age, ethnicity, year of study, or financial assistance. The findings indicate that demographic characteristics alone may not be strong predictors of NES. Future longitudinal studies with bigger, more diverse samples are needed to better understand the connections between variables and broader implications on NES.